PENERAPAN FUTURISTIK PADA E-SPORT CENTER ARENA DI KOTA MAKASSAR - Ahsyam, Muhammad Ramadhan; Alfiah, Alfiah; Abdullah, Sudarman (TIMPALAJA : Architecture Student Journals, 2025)
In building design, the futuristic approach is crucial as it focuses on creating structures that serve the future. A futuristic image reflects buildings that keep up with the times through their design expressions, with dynamic, aesthetic, and innovative values, particularly in the technologies used, such as free-form shapes and advanced, environmentally friendly systems. The application of futuristic architecture in both the exterior and interior of the e-Sport Centre continues to evolve to enable visitors to play, train, and compete in video games. A descriptive-qualitative analysis is applied to three case studies in this research. The findings show that the futuristic concept is most apparent when the form and appearance of the building contrast with the surrounding environment. More unique and asymmetric forms, along with the use of the latest structural technologies, enhance the implementation of this futuristic concept